FORMULASI DAN EVALUASI SEDIAAN SERUM WAJAH EKSTRAK ETANOL KOMBINASI DARI EKSTRAK KULIT JERUK NIPIS (Citrus aurantiifolia) DAN EKSTRAK KULIT BUAH NAGA MERAH (Hylocereus polyrhizus) - Simorangkir, Delisma; Irmayanti, Nina (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2024)
Background: The skin of the key orange (Citrus aurantiifolia) contains kuersetin, miristin, routinely, tangerine, naringin and hesperine, while the skin of the red dragon fruit (Hylocereus polyrhizus) contains betaalanin, anthocyanin, vitamin a, vitamin a, vitamin e, turnioid, flavonoid, tiamin, niacin, piridoine, kobalamin, carotene, and fitoalbumin. The research was intended to formulate it in a availability of facial serum and then evaluate its quality formula for a better facial serum from 16-4954-1998. Methods : This method of research is experimental in the laboratory by making 4 formulas consisting of F1 as serum bases, F2 ratio EKJN and EKBNM (1:1), F3 ratio EKJN and EKBNM (1:2) ,F4 ratio EKJN and EKBNM (2:1).Results : The results of all the formulas for existing existing face-serum EKJN ethanol and EKBNM viscers show a clear, clear, yellowish color, a gel-based, characteristic and homogenous odor. pH and viscosity scores on each condensed formula. No irritation test on the formula showed irritation to the skin.Conclusion : Based on this, it can be concluded that the combined ethanol extract of lime peel extract and red dragon fruit peel extract can be formulated into a facial serum cosmetic preparation and meets the quality requirements according to SNI.